The Demand for Supplementary Health Insurance, or Do Deductibles Matter? - Keeler, Emmett B.; Morrow, Daniel T.; Newhouse, Joseph P. (Journal of Political Economy, 1977)
A model in which the individual with median anticipated health expenditures an choose the level of deductible supplementation for his group is used to estimate the demand for supplementary insurance. Differences between individually purchased and group insurance are discussed. Claims and expenditure data are used to show that demand for supplementation of outpatient services will be small unless the tax subsidy of insurance is continued. Experience from Medicare corroborates these predictions.